1997
DOI: 10.1038/nbt0197-29
|View full text |Cite
|
Sign up to set email alerts
|

Display of heterologous proteins on the surface of microorganisms: From the screening of combinatorial libraries to live recombinant vaccines

Abstract: In recent years there has been considerable progress towards the development of expression systems for the display of heterologous polypeptides and, to a lesser extent, oligosaccharides on the surface of bacteria or yeast. The availability of protein display vectors has in turn provided the impetus for a range of exciting technologies. Polypeptide libraries can be displayed in bacteria and screened by cell sorting techniques, thus simplifying the isolation of proteins with high affinity for ligands. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
311
1
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 483 publications
(322 citation statements)
references
References 77 publications
3
311
1
4
Order By: Relevance
“…This approach relies on fluorescent substrates of different colors that label the surface of E. coli cells upon cleavage by a surface-anchored enzyme (20). Enzymes can be displayed on the surface of Gram-negative bacteria by established techniques (21,22), and thus, access to the fluorescent substrate is assured. The net result is that the cell fluorescence profile accurately reflects the catalytic activity and selectivity of the surface-displayed enzyme.…”
mentioning
confidence: 99%
“…This approach relies on fluorescent substrates of different colors that label the surface of E. coli cells upon cleavage by a surface-anchored enzyme (20). Enzymes can be displayed on the surface of Gram-negative bacteria by established techniques (21,22), and thus, access to the fluorescent substrate is assured. The net result is that the cell fluorescence profile accurately reflects the catalytic activity and selectivity of the surface-displayed enzyme.…”
mentioning
confidence: 99%
“…For screening, we used noninfectable F À E. coli HB101 cells carrying single-chain antibody fragments (scFv) scFv(225) of cetuximab (Wels et al, 1995) or scFv(72000) of matuzumab as Lpp-OmpA' fusions (Georgiou et al, 1997) on the surface as schematically shown in Figures 1a and b. After removal of unbound phage particles, bound phage were amplified by adding infectable F þ E. coli ER2738.…”
Section: Resultsmentioning
confidence: 99%
“…Surface display of foreign epitopes on bacteria can be useful in many applications, such as recombinant vaccines, reagents for diagnostics, whole-cell biocatalysts and bioadsorbants (Georgiou et al, 1997). Over the last decade, a range of immune-relevant sectors of foreign proteins have been successfully displayed on the bacterial cell surface by a large variety of fimbriae and flagella.…”
Section: Discussionmentioning
confidence: 99%